Four inputs - one output fuzzy logicsystem for washing machine / Nurain Zulaikha binti Husin - Nurain Zulaikha Husin (Institute of Engineering Mathematics, Universiti Malaysia Perlis, 2018)
The objectives of this study are as follows ; to propose fuzzy logic system for washing machinebased on four input variables ; to estimate the washing time based on the fuzzy logic system developed in (i) ; to compare the result obtained from four input variables with three input variables.